TRADISI BACA KITAB GUNDUL DI PONDOK PESANTREN PUTRI AL-ISHLAHIYAH SINGOSARI - Bashori Bashori (IBDA` : Jurnal Kajian Islam dan Budaya, 2017)
This study aims to investigates the supporting and inhibiting factors in non vowel Islamic’s Kitab Kuning (The Yellow Books) educa- tion at Pesantren Putri al-Ishlahiyyah Singosari. Qualitative research method is used in this study by using descriptive qualitative data. From the analysis, this study finds : 1) The implementation of the education is still in a traditional form, which is, using only pesantren’s material and exclude the public school’s general material in it’s curriculum. Moreover, language learning methods used in Madrasah Diniyah classes consist of enumeration methods ( bandongan ), rote methods ( hafalan ), and assess- ment methods; 2) This study concludes that supporting factors in this pesantren are: educational infrastructure and facilities , interconnected learning materials, highly educated santri and ustadz . Meanwhile, the in- hibiting factors are : less active and motivated students, lack of the in- structional media and related books, the existence of translation books which make students less motivated to learn the non-translated source books, Monotonous teaching methods, and lastly, insufficient duration due to short period and time allocation.